Clinical Dilemmas in Inflammatory Bowel Disease : New Challenges - Irving, Peter, 1970- (Wiley-Blackwell, 2011)
The second edition of Clinical Dilemmas in Inflammatory Bowel Disease: New Challenges, is a practical, up-to-date handbook providing expert guidance on specific clinical dilemmas and areas of difficulty that the gastroenterologist regularly faces in day-to-day practice.℗¡ In this new edition, 75% of the "dilemmas" are brand new dilemmas facing the IBD specialist concerning emerging treatment therapies, such as the use of cannabinoids and Viagra for Crohn's disease.℗¡ The remaining 25% of the dilemmas are fully updated from the previous edition, incorporating the latest clinical thinking. Each of.